(untitled) (Samarra Journal of Pure and Applied Science, 2023)
In this review, different types of sulfur compounds (thiols, sulfides, benzothiophenes, etc.) present in liquid fuel can be conveted by combustion to sulphur dioxide, which is a prevailing source of environmental pollution, so many countries proposed standard S-content to lower than 10 ppm. Although, hydrocracking process produce low-sulfur content, but still needs more desulfurization, researches have done using many technologies, among that were: A: Adsorptive desulfurization (ADS), through adsorptive over such surfaces. B: Oxidative Desulfurization (ODS), using an oxidant agent to convert sulfure into form can be removed. C: Hydrodesulfurization process (HDS), which is most efficient than other methods to remove organo sulfur (aliphatic and aromatic). D: Bio desulfurization (BDS), employed microorganisms to remove sulfur atom from organic S-compounds and can be environmental friendly. E: Extractive desulfurization (EDS), is a prosses using solvent as liquid- liquid extraction. The above technologies faced some disadvenges such as nature of volatile molecular solvent coupled with limitation of loss solvent, difficult of extraction regeneration, environmental pollution and costly, as required industrial unit operation at high temperature and pressure beside the expensive of hydrogen gas and catalysts. Therefore, it has been a challenge research investigation to explore a new deep extractive desulfurization methods. Among these treatments was using ionic liquids (ILS) which composed of heterocyclic organic cation (imidazolium, pyridinium, etc.) and different inorganic anions my be applied to decrease temperature, non-toxic, chemical stability, environmental friendly as green solvent, so, (ILS) used for many applications and deep eutectic desulfurization among that. Recently, studies showed that metal contains ionic liquids for extractive sulphur removal have a high influence and ability for sulphur removal than metal free (ILS) , which may be a good solvent in separation and removal of aromatic sulphur from fuel. The Fe, Co, Ni, Zn, Cu, etc. metals halides were used with organic cation to form complexes salts. The mechanism was investigated that the metal (ILS) have almost good extraction ability explained by the complexation of metal moiety with sulfur compounds.